Stochastic modelling of a hybrid renewable energy system - Varetsky, Y.; Hanzelka, Z. (Технічна електродинаміка, 2016)
This paper discusses the issue of modelling a hybrid renewable energy system for a micro-grid connected to a bulk power system. The objective of the work is to create a tool for assessing the feasibility of an energy hybrid system operation with an appropriate control strategy to ensure its efficiency. A hybrid of a solar, a wind and an energy storage device was examined. The integrated model uses statistical indices of solar irradiation and wind speed data to simulate power flow in the system. As the microgrid load demand is variable, power interchange with the bulk power system is managed by a power system supervisor. The control strategy and the load profile of the microgrid must be used to estimate the correct size of the hybrid system storage system. The proposed model was subjected to a case study. В статье рассмотрены вопросы моделирования гибридной электростанции с возобновляемыми источниками энергии для локальной сети, присоединенной к электроэнергетической системе. Целью работы было создание инструмента для обоснования рабочих характеристик гибридных электростанций с выбранными стратегиями регулирования для обеспечения эффективности их применения. Исследована гибридная установка, содержащая солнечную и ветровую электростанции, а также аккумулятор энергии. Поскольку электропотребление в локальной сети изменяется во времени, обмен мощности с электроэнергетической системой контролируется диспетчером. Поэтому, стратегия регулирования и график потребления в локальной сети должны приниматься во внимание для корректного расчета емкости аккумулятора энергии гибридной электростанции. Показано применение разработанной модели на примере конкретной локальной сети. В статті розглянуто питання моделювання гібридної електростанції з відновлюваними джерелами енергії для локальної мережі, що приєднана до електроенергетичної системи. Метою роботи є створення засобу обгрунтування робочих характеристик гібридних електростанцій з вибраними стратегіями регулювання для забезпечення еффективності їхнього застосування. Досліджено гібридну установку, що містить сонячну та вітрову електростанції і акумулятор енергії. Оскільки електроспоживання в локальній мережі змінюється з часом, обмін потужності з електроенергетичною системою контролюється диспетчером. Тому, стратегія регулювання і графік споживання в локальній мережі потрібно враховувати для коректного розрахунку ємності акумулятора енергії гібридної електростанції. Показано застосування розробленої моделі на прикладі конкретної локальної мережі.